Effects of ultrasound-assisted basic electrolyzed water (BEW) extraction on structural and functional properties of Antarctic krill (Euphausia superba) proteins - Li, Yufeng; Zeng, Qiao-Hui; Liu, Guang; Peng, Zhiyun; Wang, Yixiang; Zhu, Yongheng; Liu, Haiquan; Zhao, Yong; Jing Wang, Jing (Ultrasonics sonochemistry, 2021)
•Novel ultrasound-assisted basic electrolyzed water (BEW) extraction was established.•Ultrasound-assisted BEW successfully extracted marine Antarctic krill proteins.•Ultrasound-assisted BEW protected the active groups of proteins from oxidation.•Ultrasound-assisted BEW improved structural properties of Antarctic krill proteins.•Krill proteins-based emulsions were fabricated with superior long-term stability. A novel protein extraction method of ultrasound-assisted basic electrolyzed water (BEW) was proposed, and its effects on the structural and functional properties of Antarctic krill proteins were investigated. Results showed that BEW reduced 30.9% (w/w) NaOH consumption for the extraction of krill proteins, and its negative redox potential (−800 ~ −900 mV) protected the active groups (carbonyl, free sulfhydryl, etc.) of the proteins from oxidation compared to deionized water (DW). Moreover, the ultrasound-assisted BEW increased the extraction yield (9.4%), improved the solubility (8.5%), reduced the particle size (57 nm), favored the transition of α-helix and β-turn to β-sheet, promoted the surface hydrophobicity and disulfide bonds formation of krill proteins when compared to BEW without ultrasound. These changes contributed to the enhanced foam capacity, foam stability and emulsifying capacity of the krill proteins. Notably, all the physicochemical, structural and functional properties of the krill proteins were comparable to those extracted by the traditional ultrasound-assisted DW. This study suggests that the ultrasound-assisted BEW can be a potential candidate to extract proteins, especially offering an alternative way to produce marine proteins with high nutritional quality.